2012
DOI: 10.1371/journal.pone.0052951
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Imidazo[1,2-a]pyridine Inhibitors Targeting M. tuberculosis QcrB

Abstract: Mycobacterium tuberculosis is a major human pathogen and the causative agent for the pulmonary disease, tuberculosis (TB). Current treatment programs to combat TB are under threat due to the emergence of multi-drug and extensively-drug resistant TB. Through the use of high throughput whole cell screening of an extensive compound library a number of imidazo[1,2-a]pyridine (IP) compounds were obtained as potent lead molecules active against M. tuberculosis and Mycobacterium bovis BCG. The IP inhibitors (1–4) dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
183
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(186 citation statements)
references
References 51 publications
2
183
0
1
Order By: Relevance
“…More recent efforts have yielded a novel class of imidazo[1,2-a]pyridine amide (IPA) compounds (77,78) that prevent proliferation of M. tuberculosis by inhibition of the cytochrome bc 1 reductase complex in the mycobacterial respiratory chain (77, 79) (Fig. 1).…”
Section: Drugs That Target the Etcmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent efforts have yielded a novel class of imidazo[1,2-a]pyridine amide (IPA) compounds (77,78) that prevent proliferation of M. tuberculosis by inhibition of the cytochrome bc 1 reductase complex in the mycobacterial respiratory chain (77, 79) (Fig. 1).…”
Section: Drugs That Target the Etcmentioning
confidence: 99%
“…These compounds bind the QcrB subunit and induce bacterial cell death by abrogating electron flow through the ETC, resulting in reduced ATP synthesis under aerobic and anaerobic conditions (79). Two independent studies identified QcrB as the target for IPAs through the generation of spontaneous resistant mutants carrying various substitutions at the Thr313 residue (77,79). The lead compound from this series, Q203, displays potent killing of M. tuberculosis in axenic culture, in macrophages, and in the murine model of TB infection, with a spontaneous mutation rate in the order of 10 Ϫ8 (79).…”
Section: Drugs That Target the Etcmentioning
confidence: 99%
“…23 The hit compounds 34 and 35 showed potent anti TB activity with no evident signs of cytotoxicity (CC 50 25 μM for 4 different cell lines, CC 50 : 50% cytotoxicity concentration), however these compounds suffered from low stability in mouse microsomal fractions. Their medicinal chemistry efforts were pursued to improve the metabolic stability issue, resulting in the identi cation of 36 and 37.…”
Section: Imidazopyridine Amides (Ipa)mentioning
confidence: 96%
“…76 A inibição da subunidade b do citocromo (QcrB) bc1-aa3 foi identificada como alvo para derivados imidazol[1,2-α]piridina (24) (Figura 9). 77 O complexo citocromo bc1 apresenta um papel crucial para a cadeia transportadora de elétrons durante a síntese de ATP e, consequentemente, para o crescimento da micobacteria. 78 No entanto, já foi relatado que durante o crescimento aeróbio do MTB, a participação do citocromo bd oxidase pode compensar os efeitos inibitórios do complexo citocromo bc1.…”
Section: Alvos Envolvidos Com a Geração De Energiaunclassified